LANGUAGE CENTRE STUDENTS’ PERCEPTIONS OF AFFECTIVE CRITICAL THINKING STRATEGIES FOR EMPLOYMENT - Zainal Shah, Norshima; Yunaidi, Rahman Putra; Bhar, Sareen Kaur; Ab Aziz, Nur Syafiqah (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
In today’s fast-paced world, especially in professional contexts and for students at the Language Centre, the ability to think critically is extremely important. Despite being recognised as crucial, there is a lack of understanding about how students perceive using affective critical thinking strategies in their future workplaces. This study aims to explore their opinions on how effective past educational methods have been in developing these skills, which is essential for potential changes to the curriculum. The research involved surveying 73 Language Centre students from the National Defence University of Malaysia using a convenience sampling method. The collected data were analysed using various techniques such as descriptive, reliability, inferential, and thematic analyses, employing the SPSS software version 25.0. Descriptive analysis was used to understand respondents’ backgrounds, skills, and the relevance of these skills to their jobs. The reliability of the questionnaire was assessed using Cronbach’s Alpha coefficient, and the inferential study employed the Pearson Product Moment correlation to explore the relationship between independent and dependent variables. The findings indicated a link between how students perceive their skills and their importance in their careers. In summary, understanding students’ attitudes towards affective critical thinking strategies is crucial for improving educational methods within the Language Centre and beyond. Adapting teaching approaches to meet students’ needs could help develop a workforce adept at critical thinking, communication, and problem-solving, which are indispensable in today’s rapidly changing professional.